Searches for lepton flavor violation in meson decays at Belle - Sourav Patra (SciPost Physics Proceedings)
We report the results of recent searches on charged lepton flavor violation using the $e^+e^-$ collision data collected by the Belle detector. In the first section, we present a search for the lepton-flavor-violating decays $B{}^0_s → \ell^{\mp}\tau^{±}$, where $\ell = e, \mu$, using $121\ \mathrm{fb}^{-1}$ data collected at the $\Upsilon(5S)$ resonance. We also search for the lepton-flavour-violating decays $B^+ \to K^+ \tau^± \ell^\mp$, with $\ell = (e, \mu)$, using $711\ \mathrm{fb}^{-1}$ $\Upsilon(4S)$ data sample. Finally, we present a search for the charged lepton-flavor-violating decays $\Upsilon(1S)→\ell^±\ell^{\prime\mp}$ and radiative charged lepton-flavour-violating decays $\Upsilon(1S)→\gamma\ell^±\ell^{\prime\mp}$ [$\ell,\ell^\prime = e, \mu, \tau$] using $25\ \mathrm{fb}^{-1}$ data recorded at $\Upsilon(2S)$ resonance. This search uses $\Upsilon(1S)$ mesons produced in $\Upsilon(2S)→\pi^+\pi^-\Upsilon(1S)$ transitions.